Back Cover: Sequential Control over Thiol Click Chemistry by a Reversibly Photoactivated Thiol Mechanism of Spirothiopyran (Angew. Chem. Int. Ed. 1/2015). Issue 1 (4th December 2014) - Liu, Zhenzhen; Liu, Tao; Lin, Qiuning; Bao, Chunyan; Zhu, Linyong
Abstract : Sequential control over a thiol click reaction was realized by the reversible photoactivated formation of a thiol. In their Communication on page 174 ff., L. Zhu et al. describe the UV‐irradiation‐induced isomerization of spirothiopyran (SP) to its open form (MC), which can readily react with maleimide (MAL). The reversible photoactivated thiol formation of spirothiopyran confers spatiotemporal sequential control to the thiol click reaction.